Isotopic tracing of nitrogen source and interaction between surface water and groundwater of a small valley plain in the Zhangxi watershed. (April 2023) - Le, Fan; Li, Rongfu; Ruan, Xiaohong; Liu, Congqiang
Abstract: Identifying the mechanism for circulation of nutrient elements in the hydrological cycle is crucial for protection of water resource quality. In this study, 72 surface water and 21 groundwater samples were collected in three seasons for hydrochemical and multiple isotopic (δD-H2 O, δ 18 O–H2 O, δ 15 N–NO3 −, and δ 18 O–NO3 − ) analysis in the Zhangxi watershed, a small valley plain in the southeastern Yangtze River Delta. The hydrochemical type in surface water and shallow groundwater was Ca–HCO3, and the δD and δ 18 O isotope values were similar. Thus, the hydraulic connection and its material interaction were similar. Quantitative evaluation of the mass balance model showed that shallow groundwater accounted for more than 90% of surface water in the dry season but only 33.0% in the wet season. On the average, nitrate in shallow groundwater was mainly derived from organic fertilizer, whereas nitrate in surface water was mainly sourced from soil nitrogen and chemical fertilizer carried by surface runoff. At the time scale, the nitrogen sources of surface water showed seasonal variation owing to the interaction between surface water and groundwater. The contribution of organic fertilizer in the wet season was approximately 16.2%, but in the dry season increased to 32.3% and exceeded that of chemical fertilizer (24.6%). Shallow groundwater contributed more to surface water in the dry season, and transferred more nitrogen from organic fertilizer to surface water, so that they had similar nitrate sources. At the space scale, nitrate sources of surface water differed significantly with the land use types. The NO3 − and δ 15 N–NO3 − concentrations of the surface water in the mid-valley plain and downstream were significantly higher than in the natural forest area upstream, indicating the increased contribution of organic fertilizer. Agricultural activities and the interaction between surface water and groundwater in the valley plain area have a significant impact on nitrogen pollution. Reduction in nitrogen fertilizer use and establishment of a riparian protection zone are crucial to protect the water resource quality. Graphical abstract: Image 1 Highlights: Surface water was mainly recharged by shallow groundwater in the dry season. Nitrate sources of surface water showed seasonal variation due to hydrological cycle. Organic fertilizer contributed more nitrate to surface water in the dry season. Spatially, nitrate sources of surface water were related to land use types.